Differences in Cortical Thickness in Schizophrenia Patients With and Without Auditory Verbal Hallucinations - Ren, Honghong; Wang, Qianjin; Li, Chunwang; Li, Zongchang; Li, Jinguang; Dai, Lulin; Dong, Min; Zhou, Jun; He, Jingqi; Liao, Yanhui; He, Ying; Chen, Xiaogang; et al. (Frontiers in Molecular Neuroscience, 2022)
Auditory verbal hallucinations (AVHs) are one of the most common and severe symptoms of schizophrenia (SCZ), but the neuroanatomical mechanisms underlying AVHs remain unclear. The purpose of this study was to investigate whether AVHs are associated with cortical thinning of brain region in SCZ patients. The current study used 3T magnetic resonance imaging (MRI) technology to investigate 79 SCZ patients with AVHs (AVH), 60 SCZ patients without AVHs (non-AVH), and 83 healthy controls (HC). The severity of AVHs is assessed by the P3 hallucination item in the Positive and Negative Syndrome Scale (PANSS) and the Auditory Hallucinations Rating Scale (AHRS). Cortical thickness analysis was used to compare the whole brain vertex-wise cortical thickness among the groups. The relationship between the severity of AVHs and cortical thickness was also determined. Compared with the non-AVH and HC groups, the cortical thickness of the bilateral lateral orbitofrontal were significantly reduced in the AVH group (p < 0.0007, Bonferroni correction). There was no significant difference between non-AVH group and HC group. The cortical thickness of the left lateral orbitofrontal (P3: r = -0.44, p < 0.001; AHRS: r = -0.45, p < 0.001) and the right lateral orbitofrontal (P3: r = -0.36, p = 0.002; AHRS: r = -0.33, p = 0.004) were negatively correlated with the severity of AVHs (Bonferroni correction, p < 0.0125). Abnormal thickness of the bilateral lateral orbitofrontal cortex may be neuroanatomical mechanism of AVHs in SCZ patients.